On the Effect of Physical and Mechanical Properties of Fibrobeton Based on Metallurgical Waste - N. I., Isakulov; P. Z, Choriev; N. S., Ganiev; S. B, Nazarova; N. Y, Doniyorov (Central Asian Journal of Theoretical and Applied Science, 2022)
The article presents the results of physico-mechanical performance of waste-based, mechanically activated microfiller and polycarboxylate superplasticizer and fibrous concrete of basalt fibers generated in the metallurgical industry.